PENGEMBANGAN INDUSTRI BATIK TULIS SEBAGAI POTENSI DAERAH ( STUDI KASUS DI DESA KLAMPAR KABUPATEN PAMEKASAN) - Suharwati, Sri Ira (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Klampar Village is an area in Pamekasan Regency which has the highest number of batik artisans, namely 1300 people. The batik industry in Klampar Village is a home-based industry that has been hereditary and is used as the main livelihood of the community. Types of batik that have been developed are written batik and printed batik. In order to preserve batik as a potential and cultural area of Pamekasan, various efforts have been made both by the government and the community. Government support namely: establishing Klampar Village as a Kampung batik, providing capital assistance, improving the quality of batik, improving the infrastructure of the batik market (traditional and modern), marketing and promotion. While support from the public in the form of patenting copyright junjung drajat motifs and daun pacar cina.Keywords: batik industry; role of government; role of society